Orientation changes in surface-bound hybridized DNA undergoing preparation for ex situ spectroscopic measurements - Howell, Caitlin; Hamoudi, Hicham; Heissler, Stefan; Koelsch, Patrick; Zharnikov, Michael (Chemical physics letters, 2011)
Films of surface-bound homo-oligonucleotides on gold were hybridized and subjected to rinses using various volumes of water in preparation for ex situ spectroscopic analysis performed by high-resolution X-ray photoelectron spectroscopy, near-edge X-ray absorption fine structure spectroscopy, and infrared reflection-absorption spectroscopy. It was found that films rinsed with 0.5mL of water contained well-ordered DNA hybrids, while films rinsed with greater volumes (1 and 2mL) showed a decreased number of hybrids and a significant disruption of their intactness and order. These results illustrate the importance of taking into account preparation procedures when interpreting ex situ spectroscopic data of such systems.
Gesehen am 30.06.2022